Single and mixed interaction of experimental Trypanosoma brucei brucei and Trypanosoma evansi on the semen collection reaction time and spermatozoa morphology of Yankasa rams - Wada, Yunusa A.; Oniye, Sonnie J.; Rekwot, Peter I.; Okubanjo, Oluyinka O. (Journal of Advanced Veterinary and Animal Research, 2017)
Objective: This study was conducted to evaluate the pathological effects of experimental trypanosomosis on the semen collection reaction time and spermatozoa morphology of Yankasa rams. Materials and Methods: Twelve apparently healthy Yankasa rams aging 24-30 months and weighing 22-25 Kg were randomly selected and were distributed into four (4) groups. Groups I and II were challenged with experimental Trypanosoma brucei brucei (Federe strain) and T. evansi (Sokoto strain) respectively, while group III was challenged with both T. brucei brucei and T. evansi parasites. Group IV was left as uninfected control. Each infected ram received 2 mL of the infected blood containing 2x106 trypomastigotes via the jugular vein. The animals were examined for clinical observations, reaction time for semen collection and abnormalities in the morphology of the spermatozoa. Results: Infection of rams with trypanosomes showed scrotal edema, scrotal atrophy, loss of libido, increased semen collection reaction time, and significant increase of spermatozoa morphological abnormalities in all the infected rams. The rams especially in groups I and III were all deemed unfit for breeding by the end of the 98 days post infection, while the uninfected rams remained as healthy and had normal values of sperm morphology throughout the study period. Conclusion: Single or mixed interaction with T. brucei brucei or T. evansi is capable of causing infertility and reproductive failure in Yankasa rams. http://doi.org/10.5455/javar.2016.c174